STRATEGIC IMPORTANCE OF POSTGRADUATE UNITS OF PUBLIC UNIVERSITIES IN PERU - Arrarte Mera, Raúl Alberto (2009)
Units Post Grado, at the Public University Peruvian, comply sensitive strategic responsibilities is a fundamental source of own revenue to supplement the funding of the Pre-Degree Studies, is academics, updates to executives of both public and private sectors to be more competitive in their organizations and enhance their position in the labor market increasingly demanding. But at the same time it helps to improve our Institutional Image contributing to economic and social development of the country. This article is a progress of research work under development by the undersigned and fully funded by the Vice President for Research at the UNMSM.